2016
DOI: 10.21053/ceo.2015.01935
|View full text |Cite
|
Sign up to set email alerts
|

The Practicability of Transnasal Esophagoscopy and the Evaluation of Patient’s Perception: A Prospective Study

Abstract: ObjectivesTransnasal esophagoscopy (TNE) is a relatively new diagnostic procedure in the evaluation of patients with globus sensation and dysphagia. Enabling doctors to examine all of the upper aerodigestive system without the need for sedation, this technique is becoming more popular among otolaryngology specialists. The aim of this study is to evaluate the practicability of TNE and tolerability of patients to the test.MethodsThe study group consisted of 314 patients who were admitted to the swallowing center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…TOE especially if performed under sedation, increases the risk of cardiopulmonary events in elderly patients with comorbidities and thus requires careful monitoring and nursing care 30,31 . On the contrary, unsedated trans‐nasal esophagoscopy using ultra‐thin esophagoscope is a safe, feasible, and well‐tolerated procedure that can be performed under local anesthesia without sedation in sitting position by ENT–Head and Neck Clinicians as an office‐based procedure in their clinic for early detection of synchronous ESCN and our study also confirmed these findings 32,33 . In our study, the procedure was abandoned due to bleeding from the proliferative primary tumors in seven patients, which stopped spontaneously without any interventions and complete cricopharyngeal luminal obstruction in four patients, and thus 96.5% patients completed the examination.…”
Section: Discussionsupporting
confidence: 77%
“…TOE especially if performed under sedation, increases the risk of cardiopulmonary events in elderly patients with comorbidities and thus requires careful monitoring and nursing care 30,31 . On the contrary, unsedated trans‐nasal esophagoscopy using ultra‐thin esophagoscope is a safe, feasible, and well‐tolerated procedure that can be performed under local anesthesia without sedation in sitting position by ENT–Head and Neck Clinicians as an office‐based procedure in their clinic for early detection of synchronous ESCN and our study also confirmed these findings 32,33 . In our study, the procedure was abandoned due to bleeding from the proliferative primary tumors in seven patients, which stopped spontaneously without any interventions and complete cricopharyngeal luminal obstruction in four patients, and thus 96.5% patients completed the examination.…”
Section: Discussionsupporting
confidence: 77%
“…Insertion failure (median 5.8%, range 0–22%), epistaxis (median 2.7%, range 0–33%), and nasal pain (median 35%, range 0–58.3%) associated with UT‐EGD have been reported in the literature, but their ranges are too wide, so is the median visual analogue scale (VAS, 0–5) for nasal pain (1.4 ± 0.4, range 0.8–1.9) . In contrast, the average nasal pain (2.5 ± 0.8, range 1.2–3.7), insertion failure (3.1%, range 0–10.9%), and epistaxis (4.7%, range 0–8.9%) are more convergent and thus reliable to reflect the real‐world data from my study seriers . In brief, the approximately average side effect triad nasal pain (~VAS 2), insertion failure (~3%), and epistaxis (~4%) are tempting for inexperienced endoscopists and patients to accept UT‐EGD.…”
Section: Introductionmentioning
confidence: 99%